An attention U-Net model for detection of fine-scale hydrologic streamlines. (June 2021) - Xu, Zewei; Wang, Shaowen; Stanislawski, Lawrence V.; Jiang, Zhe; Jaroenchai, Nattapon; Sainju, Arpan Man; Shavers, Ethan; Usery, E. Lynn; Chen, Li; Li, Zhiyu; Su, Bin
Abstract: Surface water is an irreplaceable resource for human survival and environmental sustainability. Accurate, finely detailed cartographic representations of hydrologic streamlines are critically important in various scientific domains, such as assessing the quantity and quality of present and future water resources, modeling climate changes, evaluating agricultural suitability, mapping flood inundation, and monitoring environmental changes. Conventional approaches to detecting such streamlines cannot adequately incorporate information from the complex three-dimensional (3D) environment of streams and land surface features. Such information is vital to accurately delineate streamlines. In recent years, high accuracy lidar data has become increasingly available for deriving both 3D information and terrestrial surface reflectance. This study develops an attention U-net model to take advantage of high-accuracy lidar data for finely detailed streamline detection and evaluates model results against a baseline of multiple traditional machine learning methods. The evaluation shows that the attention U-net model outperforms the best baseline machine learning method by an average F1 score of 11.25% and achieves significantly better smoothness and connectivity between classified streamline channels. These findings suggest that our deep learning approach can harness high-accuracy lidar data for fine-scale hydrologic streamline detection, and in turn produce desirable benefits for many scientific domains. Highlights: A deep learning model for incorporating multi-scale remote sensing information is created. A novel application of the model for fine-scale hydrologic streamline detection is developed. An innovative streamline detection method for fully harnessing LiDAR data is presented.